ABO hemolytic disease of the fetus and newborn: thirteen years of data after implementing a universal bilirubin screening and management program. (May 2018) - Christensen, R.; Baer, V.; MacQueen, B.; O'Brien, E.; Ilstrup, S.
Abstract Objective ABO hemolytic disease occurs among neonates with blood groups A or B delivered to group O women. Extreme neonatal hyperbilirubinemia due to ABO disease has been reported, but its frequency is not well known. We sought to determine the odds of developing severe ABO hemolytic disease in the 13 years since adopting universal bilirubin screening/management in the Intermountain Healthcare system. Study design We conducted a retrospective analysis of neonates born between 2004 and 2016, defining "severe hemolytic disease" as; (1) total serum bilirubin (TSB) >25 mg/dL, or (2) hospital readmission for jaundice, or (3) bilirubin encephalopathy. Neonates born to group O (+) mothers were included and considered either; (1) Controls (not at risk for ABO disease because they were group O), (2) Study subjects (at risk for ABO disease because they were group A or B). Results Of 400, 531 live births, 47% were to group O women; 86% of whom were group O (+). Overall, 42, 529 (27%) neonates born to group O (+) women had their blood group determined; 29, 729 (68%) were O, 10, 682 (25%) A, and 3109 (7%) B. Peak TSBs during the first 10 days were higher in group A (11.0 ± 4.2 mg/dL) and B (11.5 ± 4.3) than group O neonates (10.3 ± 4.1). However the relative risks of a TSB ≥25 mg/dL, readmission for jaundice, or kernicterus, were the same in the control vs. study groups. Conclusions In our health system, severe hemolytic disease in neonates born to group O (+) woman is not more likely in group A or B neonates than in controls (group O). We recognize that in other practices, particularly those who do not have a universal bilirubin screening/management program, ABO hemolytic disease severity might be different than in our system.